Regional Analysis of Poverty in Ecuador: Sensitivity to the Choice of Equivalence Scales - García-Vélez, Diego F.; Quezada-Ruiz, Leidy D.; Tituaña-Castillo, María del Cisne; del Río-Rama, María de la Cruz (Frontiers in Psychology, 2022)
Economies of scale and equivalent consumption units, which are present households, must be considered in the measurement of monetary poverty, in order to obtain indicators that approximate the reality of each household. Therefore, in this research, monetary poverty in Ecuador is measured and analysed at the provincial level for the period 2009-2016. It works with data from the National Survey of Employment, Unemployment and Underemployment (ENEMDU) and the INEC methodology is used to measure poverty, but per-capita income is replaced by equivalent income, generated by applying a one-parameter scale (Buhmann et al., 1988) and two two-parameter scales (Cutler and Katz, 1992; OECD, 1984). The main results show that monetary poverty rates are significantly lower when equivalent income is applied, that there is high poverty sensitivity depending on the equivalence scale used and that the provinces with the highest levels of poverty are located in the Amazon region.